A comparative study of multi-mode cable vibration control using viscous and viscoelastic dampers through field tests on the Sutong Bridge. (1st December 2020) - Chen, Lin; Sun, Limin; Xu, Yuyuan; Di, Fangdian; Xu, Yingmei; Wang, Lujun
Highlights: Viscoelastic and viscous dampers compared in detail for cable vibration control. Damping effects considered for most cable modes with frequency lower than 3.0 Hz. Field tests on cables of 334.2 m, 454.1 m, and 569.1 m long of the Sutong Bridge. Actual damping compared to analytical estimate using damper parameters from tests. Large-amplitude damper deformation under operational loads of the bridge observed. Abstract: This study reports a comprehensive performance comparison of two types of widely used dampers, i.e., viscoelastic dampers (VEDs) and viscous dampers (VDs), for multi-mode vibration control of long cables. Cables of three different lengths (334.2 m, 454.1 m and 546.9 m respectively) in the Sutong Bridge were chosen for investigation. The VED is of viscous-shear type and it consists a housing box containing viscous medium and shear plates immersed in the viscous medium. When attached to the cable, the shear plates and the housing are respectively connected to the cable with a clamp and to a support using flange connections. The VD under study is a typical fluid damper which uses two ball joints to respectively connect to the cable and the support. The manufactured dampers were first tested in laboratory for mechanical properties based on which the damper design was adjusted for maximizing multi-mode cable damping effects. The dampers were eventually attached to the respective cable on the bridge for field tests when the bridge was in operation. Field test results show that the VED provides comparable damping effects for all tested modes while the VD provided damping decreases considerably for higher cable modes. For cable modes with frequency approximately ranging from 1.4 Hz to 3.0 Hz their performances are comparable. Comparisons have then been performed between the measurements and analytical analyses based on a model of a shallow cable with a Kelvin-Voigt damper using damper parameters identified from laboratory tests. It is found that for the VEDs theoretical predictions agree well with the measurements suggesting no efficiency loss from damper support or connections while the measured damping ratios provided by the VD are about 33% to 80% of the corresponding theoretical estimates which is probably attributed to the joints required for the VDs. In addition, measurements on damper deformation in the field tests show that the damper for such long cables experiences continuous cyclic deformation with large amplitude and low frequency due to heavy traffic load induced bridge deck deflections. This deformation could cause severe fatigue problems of the damper and its connections and hence needs to be considered in damper design.